Medicinal Plants with Anti-Poisoning Toxicity of Carbon Tetrachloride: An Overview of the Most Important Medicinal Plants Native to Iran with Anti- Carbon Tetrachloride Toxicity - Mahmoud Mirhosseini (Journal of Global Pharma Technology, 2017)
One type of the liver poisoning is poisoning with carbon tetrachloride. Carbon tetrachloride-induced liver damage is related to the toxic agent which is metabolized by the NADPH-cytochrome P450 enzyme system to reactive radicals including trikler and methyl- o- proxyler. One of the available remedies to protect liver is the use of medicinal plants. Since in Iran liver protective drugs are less available, then the use of available natural remedies that have fewer toxic side effects than chemical drugs seems necessary. In the present study, medicinal plants native to Iran have been reviewed and reported which have liver protective effect against toxicity induced by carbon tetrachloride as a factor causing human poisoning. In this review study, literatures were searched with key words including liver toxicity, carbon tetrachloride, herbs, extracts, and essential oils. The papers were searched from databases inside and outside Iran including Google Scholar, SID, MegaIran databases, and a number of other databases. Based on the results, medicinal herbs such as grape, oak, Aucheri, pistachio, Fumaria, and milk thistle are anti-poisoning plamts against carbon tetrachloride. Since the active ingredients of the mentioned plants have been specified in the phytochemical studies, then catechin, epi-catechins, epi-3-gallate catechin, mucilage, calheritrin, fumaric acid and an alkaloid called fumarinkoerist, and nitrose amine are probably the active ingredients against carbon tetrachloride poisoning.Keywords: liver, Poisoning, Carbon tetrachloride, Herbs, Iran